Therapeutic Potential of Epigallocatechin-3-Gallate in Cancer: A Systematic Review of Human Cancer - Denny Satria Utama; Krisna Murti; Irfanuddin Irfanuddin (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
In an effort to prevent and manage various types of cancer, the following study seeks to synthesize the results of various clinical trials on the efficacy and safety of the use of epigallocatechin 3-gallate. The systematic review method was employed in the following study as an effort to review the results of various clinical trials on the therapeutic response and safety of the use of EGCG in cancer patients, strictly following the PRISMA 2020 criteria. From the results of the search in the five online databases, a total of 293 articles were identified, from which seven clinical trials published between 2014 and 2024 were identified. The results of the clinical trials on the efficacy and safety of the use of EGCG in cancer patients showed that EGCG has the potential to reduce the levels of PSA in various groups of patients with prostate cancer, as well as reduce the occurrence of acute radiation esophagitis in patients with advanced lung cancer, although the results were not statistically significant. Although EGCG has an excellent safety profile with no serious side effects reported, its definitive therapeutic efficacy remains unclear, necessitating randomized controlled clinical trials to clarify its clinical relevance and health implications. Keywords: Cancer, Clinical Trial, Epigallocatechin-3-Gallate (EGCG), Public Health, Systematic Review.